NARATOR DAN KEBERULANGAN CERITA DALAM FILM PERFUME THE STORY OF A MURDERER - Sutrisno, Agung (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2020)
This research article has to describe the role of the narrator and the repetition that occurs in the film